Evaluation of the time-resolved EHD force produced by a plasma actuator by particle image velocimetry - a parametric study. (September 2015) - Benard, N; Caron, M; Moreau, E
Abstract: Surface plasma discharges, and more specifically dielectric barrier discharge, find several applications in aerodynamic due to their capability to produce a local flow at the dielectric wall. The present study proposes a numerical method to estimate the EHD force by using experimental velocity information. Here, this method is used in a parametric study and the obtained results are compared with force balance measurements. It is shown that the EHD volume force increases in space and in amplitude for increasing voltage and increasing AC frequency. Furthermore the force distribution expands in an homothetic manner.